2005
DOI: 10.1074/jbc.c400596200
|View full text |Cite
|
Sign up to set email alerts
|

R7BP, a Novel Neuronal Protein Interacting with RGS Proteins of the R7 Family

Abstract: The R7 subfamily of the regulators of G protein signaling (RGS) proteins is represented by four members broadly expressed in the mammalian nervous system. Here we report that in the brain all four R7 proteins form tight complexes with a previously unidentified protein, which we call the R7-binding protein or R7BP. We initially identified R7BP as a protein co-precipitating with the R7 protein, RGS9, from extracts obtained from the striatal region of the brain. We further showed that R7BP forms a tight complex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
193
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(200 citation statements)
references
References 29 publications
7
193
0
Order By: Relevance
“…Interestingly, the R7BP phenotype is not identical to the one observed in mice lacking RGS9, as blockade of RGS9-2 actions enhances morphine analgesia but also exacerbates morphine withdrawal, whereas genetic deletion of R7BP affects analgesia but not withdrawal. As R7BP interacts with RGS6/7 and RGS9-2 in the brain (Martemyanov et al, 2005), and it is present in the LC, we speculate that actions of R7 complexes in the LC oppose the actions of R7 complexes in the striatum and for this reason, the overall withdrawal expression does not change in R7BP mutants. Our study provides solid evidence on a role of R7BP protein in morphine tolerance, using several paradigms of morphine administration in pain-free as well as in Figure 6 R7BP does not affect morphine withdrawal.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, the R7BP phenotype is not identical to the one observed in mice lacking RGS9, as blockade of RGS9-2 actions enhances morphine analgesia but also exacerbates morphine withdrawal, whereas genetic deletion of R7BP affects analgesia but not withdrawal. As R7BP interacts with RGS6/7 and RGS9-2 in the brain (Martemyanov et al, 2005), and it is present in the LC, we speculate that actions of R7 complexes in the LC oppose the actions of R7 complexes in the striatum and for this reason, the overall withdrawal expression does not change in R7BP mutants. Our study provides solid evidence on a role of R7BP protein in morphine tolerance, using several paradigms of morphine administration in pain-free as well as in Figure 6 R7BP does not affect morphine withdrawal.…”
Section: Discussionmentioning
confidence: 94%
“…For western blot analysis studies, Gb5 (a protein shown not to be regulated by opiate administration) was used as a loading control. The following antibodies were used for IP and western blot assays: rabbit protein A-purified anti-RGS9-antibody (1 : 10 000; Psifogeorgou et al, 2007) and a rabbit anti-Gb5 (C-terminus) antibody (1 : 20 000; W Simonds, National Institute of Diabetes, Digestive and Kidney Diseases, Bethesda, MD), a rabbit anti-RGS6/7 antibody (Wyeth-Ayerst Pharmaceuticals, Madison, NJ, USA), and a rabbit anti-R7BP antibody (Martemyanov et al, 2005). For synaptosomal preparations, striatum was dissected and homogenized in 1 ml 0.32 M sucrose 0.1 mM CaCl 2 (containing phosphatase-NaF, Na 3 VO 4 -, and protease inhibitors) using a glass homogenizing tube and a Teflon pestle.…”
Section: Co-immunoprecipitation Assays and Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…The same rule should apply to both RGS9 isoforms because they share an identical R9AP-binding domain and both bind to R9AP with very high affinity (8,27). Therefore, in the rest of this study we concentrated on comparing the wild-type-like group of transgenic rods with wild-type rods.…”
Section: Single-cell Recordings Reveal Heterogeneous Expression Of Rgmentioning
confidence: 99%
“…Little is known about the functional roles of these non-catalytic domains, although they are thought to contribute to the specificity of RGS interactions (reviewed in 1, 2). RGS9 is one of the better-studied multidomain RGS proteins and exists in two splice isoforms (3)(4)(5), both of which form constitutive complexes with the type 5 G protein ␤ subunit, G␤5 (6)(7)(8). The difference between these isoforms resides in the structure of their C-termini: a short 18-aa sequence in RGS9-1 is replaced with 209 residues in RGS9-2 (Fig.…”
mentioning
confidence: 99%